Storing value: The infrastructural ecologies of commodity storage. (December 2020) - Banoub, Daniel; Martin, Sarah J
As Marx pointed out in the second volume of Capital, storage is a critical moment in the circulation of capital. Yet, despite the resurgent interest in the political economy of circulation, logistics, and infrastructures, commodity storage remains under-examined in critical human geography. This paper examines the "hidden abode" of storage by tracing attempts to control moisture and realize value in two different commodity chains: Newfoundland saltfish and American grain in the late-19th- and 20th centuries. Storing preserved codfish and grain presented different biophysical obstacles for firms, but both required interventions to discipline moisture to preserve and realize the value embodied in the commodities. Through our empirical work, we frame storage sites as infrastructural ecologies : complex, more-than-human assemblages that both constrain and enable the realization of value embodied in lively commodities. This paper contributes to debates on circulation, logistics, and infrastructures by highlighting historical geographies of storage as a novel vantage point from which to analyze the frictions and flows of value under capitalist social relations. By grounding logistics in a value-theoretical framework, this paper also contributes to recent debates regarding the value (and valuation) of nature in political economy, by highlighting the role of storage and realization in the nature–value nexus.